Manipulation of Organic Afterglow in Fluoranthene‐Containing Dopant‐Matrix Systems: From Conventional Room‐Temperature Phosphorescence to Efficient Red TADF‐Type Organic Afterglow. Issue 22 (16th March 2023) - Xu, Yaxian; Yuan, Shou; Wang, Guangming; Li, Jiuyang; Wang, Xuepu; Li, Xun; Ding, Shuhui; Chen, Xuefeng; Zhang, Kaka
Abstract: It remains challenging to fabricate highly‐efficient and long‐lived organic afterglow materials, especially in the case of red afterglow systems. Here we develop advanced charge transfer (CT) technology to boost afterglow efficiency and lifetimes in fluoranthene‐containing dopant‐matrix systems. First, organic CT molecules possess singlet‐triplet splitting energy (Δ E ST ) of around 0.5 eV, much smaller than localized excitation systems. Second, upon doping into suitable organic matrices, dipole‐dipole interactions between 1 CT states and organic matrices reduce 1 CT levels with less effect on 3 CT levels, and thus further narrow Δ E ST and enhance intersystem crossing. Third, the rigid planar structure of fluoranthene groups and the rigid microenvironment provided by organic matrices can suppress phosphorescence quenching. Forth, the multiple donor design enables spectral red‐shifts to red region and switches on TADF mechanism to improve afterglow efficiency to 13.1 % and maintain afterglow lifetime of 0.1 s. Such high‐performance afterglow materials have been rarely explored in reported studies. Abstract : This study presents the transformation from conventional room‐temperature phosphorescence to efficient red TADF‐type organic afterglow in fluoranthene‐containing dopant‐matrix systems. Red TADF‐type afterglow materials with afterglow efficiency up to 13.1 % and afterglow lifetime of 0.1 s have been achieved, which paves the way for afterglow materials' applications in diverse areas.